Risks and Challenges of Hazardous Waste Management - Marfe, Gabriella (Bentham Science Publishers, 2020)
This reference presents reviews and case studies of hazardous waste management in a selection of cities. The overarching themes of the compiled topics include 1) the problems of healthcare waste management, 2) case studies of hazardous waste mismanagement, 3) health risks associated with environmental waste, issues in environmental health and 4) grassroots environmentalism.The volume initially presents reviews and case studies from developing countries, including countries in South America (Argentina), Africa (Algeria and Nigeria), and Asia (India). The latter chapters of the book focus on env.